«Guess the Melody», or Multicomponent Cyclic and Noncyclic Infectious Processes in the Pediatric Practice - I.V. Bogadelnikov; Ye.А. Kruger; A.V. Bobrysheva; E.R. Mazinova; Ye.N. Dyadyura; G.I. Smirnov (Zaslavsky O.Yu., 2013)
The article presents a clinical case of a multi-component infection in 8-year-old child. It is shown that on the background of the progress of infection (infection with Mycobacterium tuberculosis) typical, classic cyclic process (angina follicularis) develops, which ends of eradication of causative agent from the body. However, against the background of secondary immunodeficiency, activation of poliherpesvirus infection (Epstein-Barr infection, herpes virus, cytomegalovirus) occurs, i.e., noncyclic infectious process develops, which causes severity of the condition and fever, despite the absence of clinical symptoms.